Games in everyday life : for play - Hulsey, Nathan (Emerald Publishing Limited, 2019)
In this book, Nathan Hulsey explores the links between game design, surveillance, computation, and the emerging technologies that impact our everyday lives at home, at work, and with our family and friends. The book delves into the role of gamification in motivating us to use software and applications, alter our behaviors, and to collect, display, and contextualize personal data. The author utilizes historical examples of pre-gamified technologies and techniques to explore gamification's growing effect on environments, bodies, and spaces. Reimagining gamification as a surveillance-oriented ideology that eschews traditional disciplinary techniques of control, he argues that gamification uses seduction, in the forms of game mechanics, to encourage people to submit their data in a strategy that utilizes play to promote social, economic and behavioral change. He asks: What are the consequences of leveraging play as a mode of control? What are the outcomes using of addictive design to influence our perception of work and play? As we become more reliant on the digital, will we all become players in an infinite game? If so, who wins?